2012
DOI: 10.1007/s00198-012-2204-6
|View full text |Cite
|
Sign up to set email alerts
|

How important is vitamin D in preventing infections?

Abstract: Interaction with the immune system is one of the most recently established nonclassic effects of vitamin D (VitD). For many years, this was considered to be limited to granulomatous diseases in which synthesis of active 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) or calcitriol is known to be increased. However, recent reports have supported a role for 1,25(OH)2D3 in promoting normal function of the innate and adaptive immune systems. Crucially, these effects seem to be mediated not only by the endocrine function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
22

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 156 publications
2
77
0
22
Order By: Relevance
“…Seasonal variation in vitamin D levels has been proposed to affect immune function [34]. Indeed, previous work from Iceland has shown that vitamin D levels are lowest in February to March and highest in June to July [35].…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal variation in vitamin D levels has been proposed to affect immune function [34]. Indeed, previous work from Iceland has shown that vitamin D levels are lowest in February to March and highest in June to July [35].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has been recognised to have several roles in the regulation of immune function and can enhance innate antimicrobial immune responses, while dampening excessive adaptive responses and inflammation to maintain self-tolerance and prevent auto-immunity (Lang et al 2013). During pregnancy, vitamin D is thought to enhance innate anti-microbial and anti-inflammatory responses within the placenta and reproductive tissues, which may protect the fetus from intrauterine infection and subsequent inflammation (Grayson and Hewison 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The mDCs are professional APCs [78] and the pDCs are more closely associated with immune tolerance [79,80] All cells of innate immunity are capable of; identifying and removing foreign substances present in organs, tissues, into the blood and lymph stream; interacting with pathogens and with each other and modulating the adaptive immune response by regulating timing, type, and number of cytokines [81].…”
Section: Vitamin D and Innate Immune Systemmentioning
confidence: 99%
“…Active Vitamin D has immune modulatory effects in CKD patients which will ameliorate renal fibrosis and slow-down proteinuria development. This can be done by enhancing Th2 cell differentiation, decreasing IL-6 expression, decreasing inflammatory and oxidative stress, altering T cell behavior, thus favoring tolerance development and reduce proinflammatory activity (140,(143)(144)(145).…”
Section: Vitamin D and Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation